Amyloid positron emission tomography in sporadic cerebral amyloid angiopathy: A systematic critical update - Farid, Karim (Neuroimage Clin, 2017)
Sporadic cerebral amyloid angiopathy (CAA) is a very common small vessel disease of the brain, showing preferential and progressive amyloid-βdeposition in the wall of small arterioles and capillaries of the leptomeninges and cerebral cortex. CAA now encompasses not only a specific cerebrovascular pathological trait, but also different clinical syndromes - including spontaneous lobar intracerebral haemorrhage (ICH), dementia and ‘amyloid spells’ - an expanding spectrum of brain parenchymal MRI lesions and a set of diagnostic criteria – the Boston criteria, which have resulted in increasingly detecting CAA during life. Although currently available validated diagnostic criteria perform well in multiple lobar ICH, a formal diagnosis is currently lacking unless a brain biopsy is performed. This is partly because in practice CAA MRI biomarkers provide only indirect evidence for the disease. An accurate diagnosis of CAA in different clinical settings would have substantial impact for ICH risk stratification and antithrombotic drug use in elderly people, but also for sample homogeneity in drug trials. It has recently been demonstrated that vascular (in addition to parenchymal) amyloid-βdeposition can be detected and quantified in vivo by positron emission tomography (PET) amyloid tracers. This non-invasive approach has the potential to provide a molecular signature of CAA, and could in turn have major clinical impact. However, several issues around amyloid-PET in CAA remain unsettled and hence its diagnostic utility is limited. In this article we systematically review and critically appraise the published literature on amyloid-PET (PiB and other tracers) in sporadic CAA. We focus on two key areas: (a) the diagnostic utility of amyloid-PET in CAA and (b) the use of amyloid-PET as a window to understand pathophysiological mechanism of the disease. Key issues around amyloid-PET imaging in CAA, including relevant technical aspects are also covered in depth. A total of six small-scale studies have addressed (or reported data useful to address) the diagnostic utility of late-phase amyloid PET imaging in CAA, and one additional study dealt with early PiB images as a proxy of brain perfusion. Across these studies, amyloid PET imaging has definite diagnostic utility (currently tested only in probable CAA): it helps rule out CAA if negative, whether compared to healthy controls or to hypertensive deep ICH controls. If positive, however, differentiation from underlying incipient Alzheimer's disease (AD) can be challenging and so far, no approach (regional values, ratios, visual assessment) seems sufficient and specific enough, although early PiB data seem to hold promise. Based on the available evidence reviewed, we suggest a tentative diagnostic flow algorithm for amyloid-PET use in the clinical setting of suspected CAA, combining early- and late-phase PiB-PET images. We also identified ten mechanistic amyloid-PET studies providing early but promising proof-of-concept data on CAA pathophysiology and its various manifestations including key MRI lesions, cognitive impairment and large scale brain alterations. Key open questions that should be addressed in future studies of amyloid-PET imaging in CAA are identified and highlighted.